2016
DOI: 10.1097/yct.0000000000000317
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Anesthesia, Efficacy of Electroconvulsive Therapy, and Cognitive Functions in Treatment-Resistant Depression

Abstract: The addition of ketamine may be connected with better antidepressant efficacy of ECT, compared with only thiopental anesthesia. However, patients with added ketamine had worse results on some of the indices measuring verbal memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 16 publications
0
27
0
3
Order By: Relevance
“…The largest published randomised trial so far 31 has reported that ketamine (0·3 mg/kg) as an adjunct to propofol significantly reduced the effect of ECT on a range of aspects of memory using a modified Chinese version of the Wechsler Memory Scale. By contrast, Rybakowski and colleagues, 32 in a non-randomised prospective study, found that ketamine (1–1·5 mg/kg) as an adjunct to thiopental at alternate ECT sessions worsened verbal memory and had a trend to worsen letter fluency, but did not affect executive function, visual memory, or digit span compared with thiopental alone. Similarly, results for reorientation after ECT are conflicting; one randomised trial found adjunctive ketamine (0·3 mg/kg) led to more rapid re-orientation compared with propofol alone, 33 while a randomised crossover study with ketamine (1 mg/kg) delayed reorientation compared with methohexital 34 .…”
Section: Discussionmentioning
confidence: 90%
“…The largest published randomised trial so far 31 has reported that ketamine (0·3 mg/kg) as an adjunct to propofol significantly reduced the effect of ECT on a range of aspects of memory using a modified Chinese version of the Wechsler Memory Scale. By contrast, Rybakowski and colleagues, 32 in a non-randomised prospective study, found that ketamine (1–1·5 mg/kg) as an adjunct to thiopental at alternate ECT sessions worsened verbal memory and had a trend to worsen letter fluency, but did not affect executive function, visual memory, or digit span compared with thiopental alone. Similarly, results for reorientation after ECT are conflicting; one randomised trial found adjunctive ketamine (0·3 mg/kg) led to more rapid re-orientation compared with propofol alone, 33 while a randomised crossover study with ketamine (1 mg/kg) delayed reorientation compared with methohexital 34 .…”
Section: Discussionmentioning
confidence: 90%
“…It is worth noting that although significant reductions in depressive symptoms were associated with pre-ECT infusions of ketamine, these improvements were minimal. In addition, a randomized, controlled trial of MDD patients who received pre-ECT ketamine (1–1.5 mg/kg at ECT sessions 2 and 3 or 1–1.5 mg/kg at ECT sessions 2, 4, 6, 8, 10) or thiopental (2–3 mg/kg for all ECT sessions) found that depressive symptom severity was lower after the last ECT session in the group that received ketamine prior to the five ECT sessions than in the group that received only thiopental for all ECT sessions [96], suggesting that a greater frequency of paired ketamine and ECT may offer more clinical benefit than a single pre-ECT ketamine infusion. In contrast, another study series compared pre-ECT infusions of ketamine (1 mg/kg), thiopental (4 mg/kg), or both agents; the investigators found that depression symptom scores improved for all groups (as assessed by the HAM-D) and no statistically significant differences were observed between groups [97].…”
Section: Glutamatergic Synergism and The Maintenance Of Ketamine’smentioning
confidence: 99%
“…1, Table 1). [9][10][11][12][13][14][15][16][17][18] These trials comprised 602 participants with a major depressive episode (ketamine group n = 333, comparator group n = 269). One study was retained despite important methodological concerns, including contradictory statements as to whether the trial was a single-or double-blind RCT, 14 and therefore analyses were repeated excluding this trial.…”
Section: Resultsmentioning
confidence: 99%